Pengaruh Virtual Tour dan Interaktivitas Media Digital terhadap Minat Wisatawan Dengan Brand Image (Studi pada Destinasi Badung Selatan) - Ida Bagus Gede Yoga Agastya; Ni Nyoman Sri Wisudawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the effect of Virtual Tour and Digital Media Interactivity on Tourist Visit Intention with Brand Image as a mediating variable in the South Badung destination area. The rapid development of digital technology has transformed tourism marketing, enabling destinations to provide immersive pre-visit experiences through virtual tours and interactive media. Using a quantitative approach, data were collected from 170 respondents who had used or accessed virtual tours and digital media related to South Badung. The analysis employed the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique to evaluate both direct and indirect relationships. The findings reveal that virtual tours and digital media interactivity significantly and positively influence brand image, which in turn enhances tourist visit intention. Moreover, brand image partially mediates the effect of virtual tours and digital interactivity on visit intention. These results highlight the strategic importance of high-quality digital experiences in strengthening destination brand image and stimulating actual visits. The study contributes theoretically to digital marketing and tourism literature and provides practical implications for destination managers and local governments in designing effective technology-based promotional strategies.